Oxygen K-edge X-ray absorption spectroscopy study in ice and molecular dynamics study in hydrogen hydrate : density functional theory applicaitons - Zhang, Jingyun (2012)
Many properties of the water in the physics concern are not well understood. In this thesis, oxygen K edge X-ray absorption spectroscopy (XAS) calculations of ice (water in solid form) and first principles molecular dynamics study of the hydrogen hydrate (ice-relating material) under compression are presented.